Melayu definisi, Melayu polisi dan bukan Melayu dalam Enakmen Tanah Rizab Melayu: satu tinjauan - Resali Muda, (Fakulti Undang - Undang, 2009)
The Malay Reservation Enactment (MRE) is a set of special land legislation for the Malays with the purpose of protecting their interest in land. There are three categories of ‘persons’ (both natural and legal persons) who could lawfully participate in the MRE, namely, the definitive Malay, the Policy Malay and Non-Malay. Persons coming within the category of ‘Policy Malay and Non Malay’ are able to participate in the MRE in different capacities enunciated therein. The differences among them are due to the disparity in power exercised by the state authority. Each state exercises the power independently and quite differently from each other and hence muddles the implementation of the MRE. Holistic efforts should be made to ensure the uniformity of the procedures of determining entity and capacity of each of the categories of persons that can lawfully be involved in the MRE